PENGARUH EXPERTISE DAN TRUSTWORTHINESS TERHADAP INFORMATION CREDIBILITY FOOD BLOGGER AKUN MEDIA SOSIAL INSTAGRAM KULINER DI LAMPUNG - Devi Yunika Sari (Journal Strategy of Management and Accounting Through Research and Technology (SMART), 2023)
Advances in technology, computers, and telecommunications support the development of internet technology. The internet has helped people a lot in all aspects of life so that the internet has a full share in social life. Instagram is a social networking application that is used to share photos and information that allows its users to take photos. Some people use Instagram as a tool or media to introduce or promote various things, including culinary. Because there are many culinary sellers in Lampung, this makes people confused in choosing or determining the food they want to buy and eat. There is anxiety and worry that is felt when they buy food that they have never eaten before, for fear that it will not match their expectations about the food in terms of taste, appearance, price, and service from culinary sellers. This study aims to determine the effect of Expertise and Trustworthiness on culinary review accounts in Lampung, using a quantitative approach which shows that Expertise has a positive and significant effect on Information Credibility Food Blogger Culinary Instagram Social Media Accounts in Lampung, Trustworthiness has a positive and significant effect on Information Credibility Food Blogger Culinary Instagram Social Media Accounts in Lampung and Expertise and Trustworthiness have a significant effect on Information Credibility Food Bloggers Culinary Instagram Social Media Accounts in Lampung.